PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN MENULIS TEKS PIDATO SISWA KELAS VIII SMP SULTAN ISKANDAR MUDA - Khairunissa, Khairunissa; Trianton, Teguh; Syahfitri, Dian (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2025)
The purpose of this study was to analyze the extent to which the application of the Discovery Learning model significantly influences the speech writing skills of eighth-grade students at Sultan Iskandar Muda Junior High School. This study used a quantitative approach with an experimental method, because the main focus is to test the influence or causal relationship between the use of the Discovery Learning model and students' speech writing skills. The subjects of this study were eighth-grade students of Sultan Iskandar Muda Junior High School. Class VIII was selected based on the consideration that at this level students already have basic writing skills, but still require further guidance in composing systematic and communicative speech texts. The study population consisted of 32 students, and the sampling technique used was total sampling, so that all members of the population were used as research samples. The results showed that the application of Discovery Learning (variable X) had a positive and significant influence on students' speech writing skills (variable Y) in the Indonesian Language subject. In other words, the more optimal the application of the Discovery Learning model, the better the students' ability to write speech texts effectively.